Ab Initio Molecular Dynamics Simulation of Oxygen Adsorption and Electron Transfer on SOFC Cathode. (2nd June 2015) - Sugiura, Shinya; Shibuta, Yasushi; Shimamura, Kohei; Misawa, Masaaki; Shimojo, Fuyuki; Yamaguchi, Shu
Abstract : Absorption and subsequent dissociation of oxygen molecules on the cathode surface of the solid oxide fuel cell (SOFC) with various types of vacancy are investigated by the ab initio MD simulation. The oxygen molecule adsorbed on the nickelous oxide (NiO) surface with an oxygen vacancy at the surface layer and that on the surface with a nickel vacancy at the subsurface layer are dissociated. On the other hand, the oxygen molecule adsorbed on the NiO surface with a nickel vacancy at the surface layer and that on the surface with an oxygen vacancy at the subsurface are not dissociated. The change in Mulliken charge of oxygen atoms and connecting nickel atoms during the dissociation is larger during the adsorption.